Presence of fipronil and metabolites in eggs and feathers of ornamental hens from Italian family farms. (August 2022) - Arioli, Francesco; Negro, Viviana; Roncada, Paola; Guerrini, Alessandro; Villa, Roberto; Nobile, Maria; Chiesa, Luca; Panseri, Sara
Abstract: In Italy, hens for beauty contests are bred in backyard farms, characterized by the presence of few heads and self-consumption of animal products. According to law, these small farms are not subject to animal registration on national databases and are not submitted to official inspections by official veterinarians. Fipronil belongs to the category of banned drugs for animals intended for human consumption. However, being sold the formulation for pets both online and on the market, its illicit use by farmers is conceivable. In this study, egg and feather samples were collected from 19 farms spread all over Italy, and the concentration of fipronil and its main metabolites (fipronil-sulfone, hydroxy-fipronil, fipronil-desulfinyl, and fipronil-sulfide) were analysed by HPLC-HRMS. Two farms out of 19 reached a positivity rate of 80% for fipronil; five farms reached a positivity rate of 80% for fipronil-sulfone. Analysed separately, egg albumens and yolks showed a positive correlation for the concentration of both fipronil (r 0.92) and fipronil-sulfone (r 0.74), with higher concentrations recorded in yolk due to the lipophilicity of the molecules. The risk characterization shows that the intake of these eggs is not harmful to human health: the EDI (estimated daily intake) calculated on the data we collected was below the ADI (acceptable daily intake). Fipronil-desulfinyl was detected in higher concentrations in feathers, likely as a photodegradation product of the parent molecule. Highlights: The use of Fipronil for food producing animals is not allowed in European Union. Hens' family farms for food production and beauty contest, must not be controlled. Eventual presence of Fipronil and metabolites in eggs could therefore be suspected. Eggs and feathers, as a possible matrix, were analysed and 17% of eggs exceeded MRL. Human intake evaluation, through ADI comparison, did not reveal a health concern.